2017
DOI: 10.2131/fts.4.85
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction: Quantitative morphometric analysis of vimentin filaments in Sertoli cells of rats after <i>in utero</i> DBP exposure

Abstract: -The intermediate filament of mature Sertoli cells is vimentin (Vim).One of the toxicological consequences of phthalate exposure is a selective decrease in Vim, an intermediate-sized (10 nm) cytoplasmic microfilament, in Sertoli cells. Vim in Sertoli cells of rats exposed in utero to 100 mg/kg/ day di(n-butyl) phthalate (DBP) on gestation days 12-21 was quantified. Immunohistochemical analysis revealed that Vim aggregated in Sertoli cells, but desmin filaments did not. Vim images were extracted from electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Vimentin distribution depends on the spermatogenesis cycle, and they would be distributed along with the head of the spermatozoa. Vimentin would maintain the integrity of the spermatogenic cells and their connection [ 27 ]. Another study has reported that vimentin was also found in the Leydig cells of mature or immature testes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin distribution depends on the spermatogenesis cycle, and they would be distributed along with the head of the spermatozoa. Vimentin would maintain the integrity of the spermatogenic cells and their connection [ 27 ]. Another study has reported that vimentin was also found in the Leydig cells of mature or immature testes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%